Identifikasi Miskonsepsi Peserta Didik dengan Menggunakan Metode Certainty of Respon Index (Cri) Materi Tata Surya Kelas VI Sekolah Dasar - Nurul Dian Pertiwi; Diana Endah Handayani (STKIP Andi Matappa Pangkep, 2022)
The purpose of this study was to find out the misconceptions about the solar system material and the causes of the misconceptions about the solar system material for grade VI Elementary School. Sources of data used in the study were the results of diagnostic tests on solar system misconceptions, interviews with sixth grade students and teachers. The method of analysis includes data reduction, data presentation, and drawing conclusions. The results showed that there were misconceptions that occurred in students of class VI solar system SDN Gayamsari 01 with a misconception category of 47.6%. Misconceptions often occur in the material of the solar system, namely the explanation of the solar system, the phases of the moon that students do not really understand and the direction of the earth's rotation is still wrong. The cause of the misconception that occurred in the first student, the way students learn is different because the current condition, namely the covid-19 pandemic, makes students have to study at home and make students learn only briefly. Second, low student motivation. Third, students' understanding of the material is reduced. Fourth, the teaching methods used by teachers are less varied.